Hemisynthesis and Biological Evaluation of Cinnamylated, Benzylated, and Prenylated Dihydrochalcones from a Common Bio-Sourced Precursor - Anne Ardaillou; Jérôme Alsarraf; Jean Legault; François Simard; André Pichette (MDPI AG, 2021)
Several families of naturally occurring C-alkylated dihydrochalcones display a broad range of biological activities, including antimicrobial and cytotoxic properties, depending on their alkylation sidechain. The catalytic Friedel-Crafts alkylation of the readily available aglycon moiety of neohesperidin dihydrochalcone was performed using cinnamyl, benzyl, and isoprenyl alcohols. This procedure provided a straightforward access to a series of derivatives that were structurally related to natural balsacones, uvaretin, and erioschalcones, respectively. The antibacterial and cytotoxic potential of these novel analogs was evaluated in vitro and highlighted some relations between the structure and the pharmacological properties of alkylated dihydrochalcones.